Organizational Citizenship Behavior (Ocb) Teachers And Staff (Ptk) Regional Honorariums (Honda) Elementary School (Sd) In Banyumas - Muhammad Arif Munandar; Ade Banani; Sudarto Sudarto (HOME, 2018)
This research is motivated by the existence of PTK Honda’s extra working more than supposed to be leading to OCB forms and persists in its work with salary received under regional minimum wage (UMR). The purpose of this research is to know the forms, causal factors and impact of OCB for PTK Honda SD in Banyumas.This research used qualitative method. Data collection techniques of this research used observation, documentation, and interviews. Selection of samples done by using purposive sampling (purposive sampling) 12 (twelve) selected samples. The collected data analysed through three stages of data reduction, data presentation and conclusion, while for the validity test, using source triangulation method. The results of this study indicated that OCB forms in PTK Honda such as: altruism, conscientiousness, sportsmanship, courtesy, civic virtue and two dominant results were altruism (voluntary work) and conscientiousness (timely presence). Furthermore, factors affecting OCB on PTK Honda were job satisfaction, organizational commitment, personality, morale and motivation internally while externally leadership style of head master and work culture. While for internal dominant factor was job satisfaction and organizational commitment, while external factor was leadership style. The impact of OCB behavior was the increase of work productivity, saving human resources and creating an emotional closeness among employees.